Exploring The Influence Of Suistanability Marketing Management On Brand Loyalty Among Generation Z - Khotimah, Khusnul (SEAN Institute, 2024)
This research aims to explore the influence of sustainability marketing on brand loyalty among Generation Z. A key issue identified is the growing importance of sustainability in young consumers' decision-making, as they are often presented with a wide selection of brands claiming to be committed to sustainability. In this context, the challenge for brands is how to foster long-term loyalty among Generation Z by authentically integrating sustainability values into their marketing strategies. To address this, the study employs a qualitative approach, utilizing in-depth interviews and focus group discussions (FGDs) to examine Generation Z's perceptions and experiences of sustainable marketing. The findings indicate that sustainability, when executed with transparency and integrity, can enhance brand loyalty, making consumers more likely to purchase from and continue supporting brands committed to social and environmental issues. Additionally, emotional connections and social influence play a crucial role in shaping loyalty.This research provides practical insights for companies in designing marketing strategies that strengthen relationships with Generation Z through sustainability principles.